(3QSGdI dGeJMGf GdCPcjGA hGdMPGbs - (3eMeO GdcQOj GdSgQhGfj GdTgjQ H` efdG RGOgs; (3YHO GdQMef Hf CMeO Hf eMeO GdLGej, fhQ GdOjf,J (B898 (3g` s ((3eUWai Hf eMeO GdTQGHj s)
(3ChdgG (B:s
(3hHYO, ajbhd efdG RGOI GdcQOj(B: (3gPg gj GdehGVY GdJj hbY ajgG GdZdW hGdeSGeMI Hjf GdTGQM s
(3BNQgG (B:s
(3hMce GdGHfI cMce GdGHf aj LejY eG PcQ, EdG aj MPa geRJgG hbO PcQfGg aj GdMGTjI CjVkG s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B296 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B122s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B143 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1372s
Keywords: (3GdfMhs